2017
DOI: 10.1002/btpr.2564
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus‐mediated disintegrin and metalloproteinase 17 RNA interference reversed the acquired resistance to gefitinib in lung adenocarcinoma cells in vitro

Abstract: Objective: The aim of the study is to evaluate the effects of silencing a disintegrin and metalloproteinase 17 (ADAM17) gene expression by lentivirus-mediated RNA interference (RNAi) in the gefitinib-resistant lung adenocarcinoma cells, and then to explore whether the recombinant lentivirus mediated ADAM17 RNAi reversed the acquired resistance of lung adenocarcinoma to gefitinib in vitro.Correspondence concerning this article should be addressed to Y.-Q.Li at lidoctor03@126.com. 196V C 2017 American Institute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…ADAM17 has been shown to drive therapeutic resistance in cancer [127], raising the possibility that ADAM17 may be complicit in EREG-mediated drug resistance. In EGFR-TKI-resistant NSCLC cells, an RNA interference-mediated ADAM17 knockdown recovers the sensitivity to the EGFR-TKI gefitinib through the dephosphorylation of EGFR [128]. Similarly, ADAM17 attenuation by an anti-ADAM17 antibody causes sensitization to EGFR-TKIs in NSCLC cells, which is accompanied by ERK inactivation [90].…”
Section: Ereg and Resistance To Anticancer Drugsmentioning
confidence: 99%
“…ADAM17 has been shown to drive therapeutic resistance in cancer [127], raising the possibility that ADAM17 may be complicit in EREG-mediated drug resistance. In EGFR-TKI-resistant NSCLC cells, an RNA interference-mediated ADAM17 knockdown recovers the sensitivity to the EGFR-TKI gefitinib through the dephosphorylation of EGFR [128]. Similarly, ADAM17 attenuation by an anti-ADAM17 antibody causes sensitization to EGFR-TKIs in NSCLC cells, which is accompanied by ERK inactivation [90].…”
Section: Ereg and Resistance To Anticancer Drugsmentioning
confidence: 99%
“…ADAMs can induce proteolytic processing to release the membrane-attached proteins and activate the cleaved molecules, which are involved in growth factor signalling, cell migration, cell adhesion, and other aspects ( Camodeca et al, 2019 ). Studies report that ADAM is abnormally upregulated and downregulated in various malignant tumour tissues, such as lung cancer, liver cancer, and colon cancer ( Li et al, 2018 ; Jin et al, 2020 ; Du et al, 2022 ). Such abnormal expression promotes the proliferation of tumour cells and participation in tumour angiogenesis by regulating intercellular adhesion and degrading the intercellular substance.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR), a member of the ErbB family, is a transmembrane tyrosine kinase receptor. 15 Accumulating researches had demonstrated that EGFR mutation occurred frequently in non-smoking female Asian patients with LADC. [16][17][18] Gefitinib, an EGFR tyrosine kinase inhibitor (TKI), is widely used in clinical application as a molecular-targeting drug in the treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%